ANALISIS SPASIAL GENANGAN BANJIR MENGGUNAKAN CITRA SENTINEL-1 SYNTHETIC APERTURE RADAR (SAR) DI KABUPATEN INDRAMAYU - Ramadhan, Zidan; Salma, Ghina Yusriyyah; Nulhakim, Diki Lukman; Ridwana, Riki; Aliyan, Silmi Afina (Jurnal Spasial, 2024)
Floods are one of the many disasters that often occur in Indonesia. Based on data released by BNPB (2017), approximately 31.3% of natural disasters that occur in Indonesia are floods. In general, floods also frequently occur in the administrative area of the Indramayu Regency. Indramayu, which is a coastal area and has topography with an average slope of 0-2%, certainly increases the potential for flood disasters. To help deal with the problem of frequent flooding, radar system remote sensing technology can be utilized to map flood inundation areas effectively. This research was conducted to help identify and map the location of flood inundation in Indramayu Regency using Sentinel-1 multi-temporal Synthetic Aperture Radar (SAR) imagery. Radar images are processed on the Google Earth Engine using the Backscatter algorithm method. The processing results show that an area of 87581.5 ha or 42.1% of the total area of Indramayu Regency has the potential and frequent occurrence of flooding.